Kekuatan Otot Lengan dan Keseimbangan sebagai Faktor Penentu Ketepatan Melempar Koteklema pada Pemburu Paus Tradisional di Lamalera B - Katarina Nogo Beding; Bernadete Deta (Science and Education Journal (SICEDU), 2026)
This study aimed to analyze the relationship between arm muscle strength and balance with the accuracy of koteklema (whale) harpooning among the Lamalera B community. The study employed a quantitative correlational design involving 15 fishermen selected through purposive sampling. Data were collected using a hand dynamometer test, the Stork Stand Test, and a harpooning accuracy test, and were analyzed using Pearson correlation and multiple correlation analyses. The results revealed that arm muscle strength (r = 0.905; p < 0.05) and balance (r = 0.658; p < 0.05) were positively and significantly correlated with harpooning accuracy. Simultaneously, both variables demonstrated a very strong relationship with harpooning accuracy (R = 0.935), contributing 87.4% of the variance (R² = 0.874). It can be concluded that arm muscle strength and balance are important physical factors supporting the harpooning skills of the Lamalera B community.